Hydrodynamic Performance of an Asymmetry OWC Device Mounted on a Box-Type Breakwater - Deng, Zhengzhi; Wang, Pinjie; Cheng, Pengda (Frontiers in Marine Science, 2021)
To share the construction and maintenance cost, an asymmetric oscillating water column (OWC) device integrated with a pile-fixed box-typed offshore breakwater is considered experimentally and numerically. A fully nonlinear numerical wave tank is established and validated with the open source solver OpenFOAM. The effects of the width and draft of rear box, and the incident wave height on the wave energy conversion efficiency, reflection and transmission coefficients, and energy dissipation coefficient are examined. In addition, the superiority of the present coupling system, compared to the traditional box-type breakwater, is discussed. With well comparisons, the results show that the existence of the rear breakwater is beneficial for the formation of partial standing waves and further wave energy conversion. In the range of wave heights tested, the higher the incident wave height, the larger the energy absorption efficiency except for the short-wave regimes. Moreover, the OWC-breakwater coupling system can obtain a similar wave blocking ability to the traditional one, and simultaneously extract wave energy and decrease wave reflection.